Marketing Strategies for Promoting Sustainable Tourism Innovations: Case Study of Successful Implementation and Challenges - Lebeshkovska, Gabriela (Research Papers, 2024)
Successful implementation of sustainable tourism innovation marketing strategies is critical to addressing the growing awareness of environmental and community impacts associated with traditional tourism. Businesses aiming to thrive in this evolving landscape must adopt innovative marketing approaches not only to promote sustainable practices but also to differentiate themselves in the marketplace.